A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Expression of a single-chain monellin (MNEI) mutant with enhanced stability in transgenic mice milk - Rui Lu; Xiaoming Li; Jian Hu; Yancui Wang; Le Jin (Transgenic Research, 2024)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Constitutive expression of antimicrobial peptide PR-39 in transgenic mice significantly enhances resistance to bacterial infection and promotes growth - Fang Zeng; Rui Dong; Chengcheng Zhao; Dewu Liu; Enqin Zheng; Changxu Song; Zhenfang Wu; Zicong Li (Transgenic Research, 2018)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Seed-specific silencing of OsMRP5 reduces seed phytic acid and weight in rice - Wen-Xu Li; Hai-Jun Zhao; Wei-Qin Pang; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Transgenic Research, 2014)

Isopentenyl transferase gene (ipt) downstream transcriptionally fused with gene expression improves the growth of transgenic plants - Jian-Chun Guo; Rui-Jun Duan; Xin-Wen Hu; Kai-Mian Li; Shao-Ping Fu (Transgenic Research, 2010)

High level expression of a functional human/mouse chimeric anti-CD20 monoclonal antibody in milk of transgenic mice - Bo Tang; Shanshan Yu; Min Zheng; Fangrong Ding; Rui Zhao; Jianmin Zhao; Yunping Dai; Ning Li (Transgenic Research, 2008)